Incidence of Canine Babesiois based on Rapid Antibody Diagnostic Test in and around Navsari, Gujarat - Patel, Ashok R; Patel, Manish D; Mehta, Sudhir A; Parmar, Saurabh M; Mavadiya, Suresh V; Vala, Jignesh A; Gamit, Pooja G (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
The present study was carried out with an aim to report incidence of canine babesiosis based on rapid antibody diagnostic test in  and around Navsari, Gujarat, over a period from October 2022 to June 2023. Out of 1040 cases of dogs registered at Veterinary Clinical  Complex (VCC), Navsari, 52 cases were suspected for canine babesiosis based on clinical symptoms, blood smear examination and  haematological findings. Blood samples from these suspected cases were subjected to rapid antibody diagnostic test. The overall  incidence of canine babesiosis was 2.79 % (29/1040). Among 52 suspected cases, the incidence was 55.77 % (29/52). Comparatively,  higher incidence was observed in dogs aged between 3-6 years (34.48 %) followed by 1-3 years (20.70 %), ≤1 year (17.24 %), 6-9 years  (17.24 %) and >9 years (10.34 %). The incidence was higher in males (58.62%) than females (41.38%). Season-wise, the incidence was  higher in summer (62.07%) followed by winter (34.48%) and monsoon (3.45%). The incidence was the highest in Labrador retriever  (34.48%) followed by German shepherd (17.24%), Non-descript (17.24%) and Lhasa Apso & others (3.45% each).
Keywords: Babesiosis; Canine; Gujarat; Incidence; Rapid antibody diagnostic test